2017
DOI: 10.1016/j.anbehav.2017.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Huddling is more important than rest site selection for thermoregulation in southern bamboo lemurs

Abstract: Resting site selection can have important effects on the behaviour and fitness of organisms. The maintenance of optimal body temperatures (Tb) when faced with environmental variables has often been attributed to either specific microhabitat rest site characteristics or to behavioural strategies. Among many small group living endotherms, social thermoregulation (i.e., huddling) is utilised as a behavioural energy conservation mechanism at low ambient temperatures (Ta), thus decreasing the metabolic cost of main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 112 publications
0
8
1
2
Order By: Relevance
“…Other rodents, including mice [ 5 ], rats [ 6 ], rabbits [ 7 ] and degus [ 8 ], huddle to insulate from the cold, by collectively reducing the exposed surface-area-to-volume ratio of the group [ 9 , 10 ]. And social thermoregulation in primates (bamboo lemurs) has recently been shown to be more important for temperature homeostasis than the choice of resting site [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other rodents, including mice [ 5 ], rats [ 6 ], rabbits [ 7 ] and degus [ 8 ], huddle to insulate from the cold, by collectively reducing the exposed surface-area-to-volume ratio of the group [ 9 , 10 ]. And social thermoregulation in primates (bamboo lemurs) has recently been shown to be more important for temperature homeostasis than the choice of resting site [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The requirement for thermoregulation may also explain why the smaller species of lorisiform such as Loris, Galago, Galagoides, Paragalago and Sciurocheirus (which lose heat more quickly than their larger relatives) tend to sleep together, thereby sharing body heat (Nowack, Wippich, Mzilikazi, & Dausmann, ; cf. Eppley, Watzek, Dausmann, Ganzhorn, & Donati, ). Some of these smaller taxa, including Pg.…”
Section: Discussionmentioning
confidence: 99%
“…In Microcebus murinus, for example, TEE does not differ between the dry and the wet seasons in normothermic individuals [Schmid and Speakman, 2000]. Other studies have shown that gregarious lemurs reduce thermal stress by using behavioral thermoregulation like social huddles and peculiar resting postures and, according to some authors, by performing daylight and nocturnal activity [Donati et al, 2011;LaFleur et al, 2014;Kelley et al, 2016;Eppley et al, 2017;but see Fletcher et al, 2012].…”
Section: Discussionmentioning
confidence: 99%